Structural and Passability Analysis of Pipeline Robot - Zhiqiang Li; Weiguo Li; Zhicheng Feng; Lili Wang; Wen'gang Yan; Shijie Guo (Jixie chuandong)
Aiming at the problems of the existing oil and gas pipeline inspection robots，such as single motion mode，small pipe diameter adaptation range，poor passing ability and adaptability of the robots in pipelines，a new pipeline robot with variable motion mode is designed. The design requirements is presented and the overall structure and working principle of the robot is introduced，the support organization with the combination of main and auxiliary springs to achieve common preloading and drive structure with adjustable angle function are further proposed and analyze force. At the same time，the dimension constraints and motion constraints of the robot through the elbow pipe are analyzed. Finally，experimental verification is carried out. Experimental results show that the structure design and calculation of the robot are reasonable，the size and motion constraint analysis of the robot in the bend pipe are correct，the robot can successfully pass the bend pipe with R≥1.5D. The research results provide a reference for the follow-up robot simulation experiment and prototype manufacture.